Wahrheit und Nützlichkeit Selbstbeschreibungen der Wissenschaft zwischen Autonomie und gesellschaftlicher Relevanz - Kaldewey, David (Science Studies, 2013)
Modern science is defined on one hand as an autotelic pursuit of truth. On the other hand, it also keeps the practical benefit of new knowledge in its sights. David Kaldewey reconstructs the origin and significance of this dual goal by means of historical-sociological semantic analysis. He shows how both objectives condense among a variety of autonomy and practice discourses. The tension between these discourses reveals itself from a differentiation theoretical perspective as constitutive of the dynamics of modern science.